Launching W Singapore – Sentosa Cove: Starwood Hotel’s digital strategy to drive bookings - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2014)
In March 2012, Janice Chan, the Senior Director of Digital Marketing and Distribution for Starwood Asia Pacific Hotels, is responsible for delivering a digital marketing campaign strategy to the Sales and Marketing team at the W Singapore – Sentosa Cove. The hotel, which is set to open in just six months, needs a solid online advertising campaign that is sure to bring in 15-20% of the hotel’s booked room nights from the first month. Chan and her team have a limited budget of US$44,000 for the campaign. She recognises that a proper budget allocation across different ad platforms, as well as selecting the right feeder markets into Singapore, will be critical to success. It will take some creativity, but Chan is confident that her team will recommend a winning strategy that is sure to fill rooms when the W opens in September 2012.